DEVELOPMENTS IN COMMODITY TRADE BETWEEN IRAQ AND THE UNITED STATES AND THE FACTORS AFFECTING IT DURING THE PERIOD (2012-2022) (World Economics and Finance Bulletin, 2023)
The research studies the developments of commodity trade activities between Iraq and the United States, and highlights the most important obstacles and challenges that it encountered during the period 2012-2022. The importance of the research is evident in its study of the issue of commodity trade developments between Iraq and the United States, which is one of the important topics in the fields of international economy, as a result of the fact that Iraq is one of the largest producers and exporters of crude oil at the international level, in addition to the great importance that the United States occupies in the areas of demand for crude oil. The research problem is concentrated in the relatively unstable pace of commodity exchange between Iraq and the United States, as a result of its impact on various international variables, which limited the possibilities of developing Iraqi-American trade relations. The research aims to study the developments of commodity trade between Iraq and the United States, in addition to identifying and analyzing the role of international factors and variables in influencing the movement of commodity trade between the two countries. The research is based on the hypothesis that the relationship between international oil prices and the volume of commodity exchange between Iraq and the United States is a direct relationship. The higher the oil prices, the higher the volume of commodity exchange between the two countries, assuming the stability of other international factors. The research relied on the analytical descriptive approach by analyzing statistical data and time-series financial and economic indicators in order to obtain and analyze results. The research reached a number of results, the most important of which is the exposure of Iraq's exports to the United States to waves, from rise and fall, most of which are exports of Iraqi crude oil. The year 2012 recorded the highest level of exports, amounting to (19.265) billion dollars, while exports decreased in 2020 to the lowest level, amounting to (3.099) billion dollars. International political and security factors cast a shadow on Iraqi-American economic relations, as Iraq has witnessed severe and continuous political and security challenges since 2003, which disrupted part of the possibilities of trade exchange between Iraq and the United States, and commodity exchange between Iraq and the United States was affected by the repercussions of the spread of the Corona virus in a relatively large way during the year 2020.
Keywords: The Iraqi economy; commodity trade between Iraq and the United States; international economic relations